Economic theories of social entrepreneurship - Hamid, Zarinah; Zhang, Hengchao; Mhd. Sarif, Suhaimi (Global Academic Excellence (GAE), 2017)
The lack of researches in social entrepreneurship is particularly true in the field of economic theory. In fact, there has been no researches undertaken to explore social entrepreneurship from the perspective of economic theory. This paper attempts to shed some light on several important issues that are critical for the development of economic theories on social entrepreneurship. It discusses several major issues including the evolution of economic theories on entrepreneurship, the definition and distinct features associated with social entrepreneurship, the roles of entrepreneurship in the modern economic system and the approaches to conceptualize social entrepreneurship. Due to the significant role of social entrepreneurship in uplifting the living standard of the underprivileged community, addressing externalities within the economic system, and justly reallocating resources and welfare in the economic system, the economic theory on social entrepreneurship is believed to be a critical body of knowledge for both future practitioners and policy makers in structuring due initiatives for the healthy development of the society. It is expected that the issues discussed in this paper will not only help future researches realize the need of economic theory on the field and design a proper approach to conceptualize the subject, but also identify the potential directions to develop economic theories on social entrepreneurship.